The role of innovate leadership towards teacher’s professional development in secondary schools in Georgetown, Malaysia - Jusoh, Rosnani; Kasirajah, Subathra Rani; Md Dasuki, Nordaslina; Qiao, Shu (RSIS International, 2024)
Educational organisations are committed to providing high-quality education and preparing students for success in a competitive global environment. In recent years, there has been a growing recognition of the role of innovative leadership in promoting the effectiveness of teachers’ professional development. Furthermore, this paper aims to examine the impact of innovative leadership on the effectiveness of teachers’ professional development. This study also aims to identify the level of innovation in leadership and the effectiveness of teachers’ professional development. The population of this study is 474 teachers, and the sample size of this study is 214 teachers in Georgetown District. The data was collected with surveys using questionnaires (Statistical Package for Social Science 28) is used to obtain descriptive and inference statistics, including the mean, standard deviation, and Pearson correlation coefficient. The findings of the data show a high level of innovative leadership and effectiveness in teachers’ professional development in secondary schools at Georgetown. The innovative leadership variable shows it affects the effectiveness of teachers’ professional development variables directly through the teacher's emotions. This study yielded significant insights with broad implications for educational leadership and practice. This study resonates with various theoretical frameworks and empirical studies, affirming the pivotal role of visionary and supportive leadership in fostering an environment conducive to continuous learning and improvement in teaching practices. In conclusion, the study reaffirms the significance of innovation leadership as a key driver in the realm of educational development.